'We're all carrying a burden that we're not sharing': a qualitative study of the impact of cutaneous T‐cell lymphoma on the family. (1st April 2015) - Selman, L.E.; Beynon, T.; Radcliffe, E.; Whittaker, S.; Orlowska, D.; Child, F.; Harding, R.
Summary: Background: Cutaneous T‐cell lymphoma (CTCL) is a rare, progressive cancer that can be life limiting and highly disfiguring. Patients with CTCL experience poor quality of life; however, there is little published about the experiences of their families. Objectives: To describe the impact of CTCL on family members and how they cope and adjust, to inform support services. Methods: Semistructured qualitative interviews were conducted with adult informal caregivers of patients with CTCL recruited via a supraregional CTCL clinic. Interviews explored the history of each patient's illness, the impact of CTCL on the patient and the family, and views about family support. Data were analysed thematically using the Family Adjustment and Adaptation Response model as an interpretative framework. Results: Fourteen caregivers were interviewed (11 spouses, one friend, two daughters; 10 women, four men; all white British; aged 39–85 years). Three key themes emerged: (i) demands of CTCL (the disease, caregiving, financial impact, physical and emotional intimacy); (ii) family capabilities (family support, information, healthcare provider support, other coping strategies); and (iii) adjustment and adaptation (acceptance, changes in patient–caregiver relationship and family dynamics). CTCL was central in many aspects of caregivers' lives, particularly relationships, communication and intimacy. Conclusions: Our findings demonstrate the multiple demands that CTCL places on caregivers, the capabilities and resources they draw upon to cope, and the significant impact of CTCL on the family. To support families and patients, easily accessible services are needed that include the family in the unit of care, provide support and information, and understand the process of family adjustment and adaptation. Abstract : What's already known about this topic? Cutaneous T‐cell lymphoma (CTCL) is a rare, progressive cancer that can be life limiting and highly disfiguring. CTCL has a negative impact on patients' quality of life. What does this study add? Family caregivers of patients with CTCL experience multiple demands from the disease and the burden of caregiving. CTCL has a profound impact on family dynamics and relationships. Support services for families are needed that provide tailored information and understand family adjustment processes.